Income Outside the Agricultural Sector in Increasing the Household Income of Cashew Farmers in Lalemba Village Lawa District West Muna Regency - Muhammad Faisal; Abdul Gafaruddin; Yusran Yusran (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
This research is motivated by the fact that most of the people who farmed cashew nuts in Lalemba, West Muna Regency have the primary goal of meeting the needs of daily life aincreasingase household income. This study aims to determine the income of cashew farming and the household income of cashew farmers. This research was conducted in Lalemba Village, Lawa District, West Muna Regency, from May to December 2021. The variables in this study included age, education level, number of family members, land area, cashew farming income, and household income. This research uses farm income analysis and household income analysis. The sample of guava farmers was 38 respondents. The results of the study showed that the average income of cashew farmers was IDR. 6,302,119/Ha/Year. The.a verage household income is IDR. 18,459,883/year. The average household income consists of other farming income of IDR. 7,039.080/Ha/Year, and the average non-agricultural income is IDR. 5,018,684/Year.